BUDDHIST INTEGRATION FOR PROMOTING COMPETENCY DEVELOPMENT IN LEARNING DIGITAL TECHNOLOGY AIRPORTS OF THAILAND PUBLIC COMPANY LIMITED PERSONNEL - Benjakul, Sarawut (Journal of MCU Social Science Review, 2024)
Objectives of this research article were: 1. To study Buddhist Integration for Promoting Competency Development in Learning Digital Technology of Airports of Thailand Public Company Limited Personnel; 2. To examine factors affecting Buddhist Integration for Promoting Competency Development in Learning Digital Technology of Airports of Thailand Public Company Limited Personnel and 3. To present Buddhist Integration for Promoting Competency Development In Learning Digital Technology of Airports of Thailand Public Company Limited Personnel, conducted using mixed research methods. The quantitative research, the questionnaire was used with a reliability value of 0.972 to collect data were from 381 samples randomly sampled, derived from a total population of 7,932 people using Taro Yamane formula. Data were analyzed using frequency, percentage, mean, standard deviation, and multiple regression analysis. The qualitative research collected data from 18 key informants and 9 participants in focus group discussion and analyzed by content descriptive interpretation. Findings were as follows: 1. Competency Development in Learning Digital Technology of Airports of Thailand Public Company Limited Personnel was found at a high level overall. 2. Factors affecting Promoting Competency Development in Learning Digital Technology of Airports of Thailand Public Company Limited Personnel consisted of 1. Personnel Development in 3 aspects with statistical significance at the 0.01 level, therefore, the research hypothesis is accepted. 2. 3 aspects of Threefold Training, Tiisikkha, with statistically significant level at the 0.01, therefore, the research hypothesis is accepted. 3. Developing the digital technology learning capacity of company personnel of Airports of Thailand Public Company Limited in all 4 aspects, Use, Understand, Create and Access by applying Three-Fold Training, Tisikkha in all 3 aspects and Personnel Development in all 3 aspects as the basis Promoting the Competency Development In Learning Digital Technology of Airports of Thailand Public Company Limited Personnel to be successful.